Using defunct municipal field roads to implement low cost anti erosion measures in the ownership fragmented landscape of the Czech Republic - Jiří Brychta; Jan Pacina; Petr Novák; Milada Šťastná; Pavel Raška; Martin Dolejš; Martina Brychtová; Aneta Švarcová; Petr Švehlík; Tadeáš Děd (Scientific Reports)
Abstract The intent of the research is to introduce a new strategy which will allow the implementation of small retention elements in the landscape more quickly than the standard approach of comprehensive land consolidation (LC). The average implementation of an LC project takes more 5 years, and the implementation rate of the proposed measures are in single digits. Thus, over the short to medium term, LC will not solve the current problems of climate change and water erosion. One of the main aspects that extends the length of time taken to implement LC in the Czech Republic is the high degree of fragmentation in the ownership of agricultural land. A single block of land can be divided into dozens of individual parcels with individual owners. This very high level of fragmentation leads to a reluctance by the individual owners to farm these small parcels and thus they rent the land out to large agricultural enterprises. This leads to the creation of excessively large blocks of land, which in turn leads to acceleration of water runoff and erosion. Through an analysis of old maps and archival aerial photographs, an area of approximately 250,000 hectares of defunct field paths on arable land were identified. Since these field roads are solely owned by municipalities, they have the potential for the rapid implementation of erosion protection without administrative delays. As these paths frequently follow contour lines, they are often suitable locations for the placement of effective anti-erosion measures. On average, a reduction in erosion-prone areas of 10.85% in each cadastral territory would be possible, with a standard deviation of 10.13%. A potential reduction in areas at risk of more than 10% was identified in 4472 cadastral territories out of a total of 13,077. Using this proposed strategy, erosion-prone areas in the Czech Republic could be reduced by an average of 32.55 hectares per cadastral area, with water erosion potentially decreasing by 107.42 t yr⁻¹ per cadastral area. This equates to a total reduction of 480,382.24 t yr⁻¹ annually across the entire country.